1997
DOI: 10.1074/jbc.272.28.17887
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Stress-activated Protein Kinase and p38/RK Mitogen-activated Protein Kinase Signaling Pathways in the Enhanced Phosphorylation of Initiation Factor 4E in NIH 3T3 Cells

Abstract: The initiation factor (eIF) 4E is regulated by modulating both the phosphorylation and the availability of the protein to participate in the initiation process. Here we show that either serum treatment or activation of the stress-activated protein kinase (JNK/SAPK) led to enhanced phosphorylation of eIF4E in quiescent NIH 3T3 cells. Although the immunosuppressant, rapamycin, was found to stabilize the association of eIF4E with its negative regulator, 4E-BP1, this drug did not prevent the early effects of serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
110
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(119 citation statements)
references
References 43 publications
(51 reference statements)
9
110
0
Order By: Relevance
“…Finally, some stress conditions will lead to a severe inhibition of protein synthesis although the phosphorylation of eIF4E increased under those conditions (8,9,31). An explanation for these apparent contradicting results might come from recent data, which suggest that the intact eIF4F complex may be required for de novo initiation events but not for reinitiation (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, some stress conditions will lead to a severe inhibition of protein synthesis although the phosphorylation of eIF4E increased under those conditions (8,9,31). An explanation for these apparent contradicting results might come from recent data, which suggest that the intact eIF4F complex may be required for de novo initiation events but not for reinitiation (32).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of eIF4E is increased by mitogenic stimuli that activate translation (reviewed in Ref. 7) and by cytokines (8,9). Recently, two kinases were identified that phosphorylate Ser 209 in eIF4E and are targets for the mitogen-activated extracellular signal-regulated kinase and stress/cytokine-activated p38 mitogen-activated protein kinase pathways (9 -13).…”
mentioning
confidence: 99%
“…SDS-PAGE, Isoelectric Focusing, and Immunoblotting-Samples containing equal amounts of protein were resolved by SDS-PAGE and processed as described previously (21,22). Antiserum specific for the C-terminal domain of eIF4GI and those specific to eIF4E, eIF2␣, and phospho-eIF2␣ were as described previously (22); total levels of eIF4G, eIF4E, eIF2␣, PABP, eIF4A, and 4E-BP1 were visualized with alkaline phosphatase-conjugated secondary antibodies, while the determinations using commercial phosphospecific antisera and those for p38 MAP kinase used enhanced chemiluminescence for detection.…”
Section: Methodsmentioning
confidence: 99%
“…In all cases, care was taken to ensure that detection was within the linear range of the response. One-dimensional vertical isoelectric focusing gels used for the analysis of eIF4E phosphorylation were performed as described previously (21,22).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation